2018
DOI: 10.3390/jof4010014
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Genes for Aggressiveness in a Natural Fusarium culmorum Population Greatly Differ between Wheat and Rye Head Blight

Abstract: Fusarium culmorum is one of the species causing Fusarium head blight (FHB) in cereals in Europe. We aimed to investigate the association between the nucleotide diversity of ten F. culmorum candidate genes and field ratings of aggressiveness in winter rye. A total of 100 F. culmorum isolates collected from natural infections were phenotyped for FHB at two locations and two years. Variance components for aggressiveness showed significant isolate and isolate-by-environment variance, as expected for quantitative h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 91 publications
1
23
0
Order By: Relevance
“…In the cereal– Fusarium pathosystem, a key factor that determines the parasitic fitness of an isolate is aggressiveness, which is a quantitative measurement of the level of disease caused by the pathogen (Pariaud et al, ; van der Plank, ). Aggressiveness is frequently evaluated by directly assessing symptom development at different time points (=epidemic rate) (Castiblanco, Castillo, & Miedaner, ; Miedaner & Schilling, ; Miedaner, Gang, & Geiger, ; Pariaud et al, ). It reflects several basic quantitative traits of the fungal life cycle, such as infection efficiency, spore production rate, sizes of the lesion and for some cases, also toxin accumulation (Cumagun & Miedaner, ; Lannou, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cereal– Fusarium pathosystem, a key factor that determines the parasitic fitness of an isolate is aggressiveness, which is a quantitative measurement of the level of disease caused by the pathogen (Pariaud et al, ; van der Plank, ). Aggressiveness is frequently evaluated by directly assessing symptom development at different time points (=epidemic rate) (Castiblanco, Castillo, & Miedaner, ; Miedaner & Schilling, ; Miedaner, Gang, & Geiger, ; Pariaud et al, ). It reflects several basic quantitative traits of the fungal life cycle, such as infection efficiency, spore production rate, sizes of the lesion and for some cases, also toxin accumulation (Cumagun & Miedaner, ; Lannou, ).…”
Section: Introductionmentioning
confidence: 99%
“…Aggressiveness is of complex inheritance with many genes, each contributing only to a small part of the total variation. Recently, a candidate gene‐based association study reported an association of mitogen‐activated protein kinase (MAPK) HOG1 gene with aggressiveness and deoxynivalenol (DON) accumulation, explaining 10.29 and 6.05% of the genotypic variance in wheat, respectively, and of a cutinase gene explaining 16.05% of genotypic variance in rye (Castiblanco et al, ; Castiblanco, Marulanda, Würschum, & Miedaner, ). The role of DON in the different phases of the Fusarium life cycle (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The IDI_10dai is a quantitative trait that is easier to measure (only one time point) and, due to its high correlation with AUDPC, can be considered a highly efficient aggressiveness trait that could be applied in future studies. The latent period is also one of the most used aggressiveness quantitative traits in the literature, and provides important information regarding isolate adaptation, as isolates with shorter latent period have a selective advantage in the field, by quickly releasing the conidia into the environment (Pariaud et al, 2009a;Fr ezal et al, 2012;Delmas et al, 2016). The latent period is sometimes considered identical to the incubation period (Luo & TeBeest, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For several plant pathogen species, aggressiveness is a polygenic quantitative trait, influenced not only by the host genotype but also by the environment (e.g. temperature and humidity; Boedo et al, 2012;Delmas et al, 2016), and therefore it is considered to be shaped by natural selection resulting in different adaptive patterns according to the environment (Pariaud et al, 2009b(Pariaud et al, , 2012Boedo et al, 2012;Delmas et al, 2016). A quantitative adaptation to the host is theoretically expected to be slower than the acquisition of new qualitative virulence factors (Pariaud et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation